How to learn with intentional mistakes: NoisyEnsembles to overcome poor tissue quality for deep learning in computational pathology - Mayer, Robin S.; Gretser, Steffen; Heckmann, Lara E.; Ziegler, Paul K.; Walter, Britta; Reis, Henning; Bankov, Katrin; Becker, Sven; Triesch, Jochen; Wild, Peter J.; Flinner, Nadine (Frontiers in Medicine, 2022)
There is a lot of recent interest in the field of computational pathology, as many algorithms are introduced to detect e.g. cancer lesions or molecular features. However, there is a large gap between artificial intelligence (AI) technology and practice, since only a small fraction of the applications is used in routine diagnostics. The main problems are the transferability of convolutional neural network (cNN) models to data from other sources and the identification of uncertain predictions. The role of tissue quality itself is also largely unknown. Here we demonstrated that samples of the TCGA ovarian cancer (TCGA-OV) data set from different tissue sources have different quality characteristics and that cNN performance is linked to this property. cNNs performed best on high-quality data. Quality control tools were partially able to identify low-quality tiles, but their use did not increase the performance of the trained cNNs. Furthermore, we trained NoisyEnsembles by introducing label noise during training. These NoisyEnsembles could improve cNN performance for lower-quality, unknown datasets. Moreover, the performance increases as the ensemble becomes more consistent, suggesting that incorrect predictions could be discarded efficiently to avoid wrong diagnostic decisions.